Kinetics of Release of Water and Nutrients from Codfish (Gadus morhua L.) through a Heavy-Salting - Ferraro, Vincenza; Cruz, Isabel B.; Ferreira Jorge, Ruben; Pintado, Manuela E.; Castro, Paula M.L. (Journal of Food Processing and Preservation, 2014)
Through the typical 6 days heavy-salting, codfish releases 25% (w/w) of its physiological water due to the incorporation of high amounts of salt, 20% (w/w). Besides changes in water-holding capacity, major effects imparted by salt are modifications in muscle proteins conformation with subsequent denaturation and loss, and release of free amino acids.Water is liberated from codfish according to a power-law kinetics, which describes biological reactions under molecular crowding. Proteins and amino acids are released by pseudo-first and pseudo-second order kinetics, which describe proteolysis.Despite the loss of nutrients through salting, the nutritional value of codfish can be considered unchanged. A reduction by weight of 0.45% in muscle proteins, 1.24% aspartic acid, 1.4% glutamic acid, 2% arginine, 11% creatine, 0.2% glycine, 0.5% lysine, 0.4% methionine, 0.3% phenylalanine, 3.4% taurine and 3% tryptophan is noticed.